2019
DOI: 10.1038/s41467-019-12054-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific transcriptional programs in mouse prefrontal cortex during adolescence and addiction

Abstract: Coordinated activity-induced transcriptional changes across multiple neuron subtypes of the prefrontal cortex (PFC) play a pivotal role in encoding and regulating major cognitive behaviors. Yet, the specific transcriptional programs in each neuron subtype remain unknown. Using single-cell RNA sequencing (scRNA-seq), here we comprehensively classify all unique cell subtypes in the PFC. We analyze transcriptional dynamics of each cell subtype under a naturally adaptive and an induced condition. Adaptive changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
160
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(182 citation statements)
references
References 78 publications
19
160
3
Order By: Relevance
“…How do we reconcile these contrasting views? Our PFC single-cell dataset uncovered transcriptomic cell types consistent with those from studies that profiled the mouse brain exhaustively (Saunders et al, 2018;Zeisel et al, 2018), other parts of the neocortex , or PFC more specifically (Bhattacherjee et al, 2019), but we solely focused on using Layer 5 pyramidal neuron subtypes and their projection mapping as a case study to interrogate task encoding properties with a cell-type framework. Using PAG-projecting neurons as an example of molecular homogeneity due to our observation of its invariant clustering across multiple resolutions and methods (Figures 1E, S1B), we found that even a homogeneous transcriptomic class encodes diverse information.…”
Section: Discussionmentioning
confidence: 99%
“…How do we reconcile these contrasting views? Our PFC single-cell dataset uncovered transcriptomic cell types consistent with those from studies that profiled the mouse brain exhaustively (Saunders et al, 2018;Zeisel et al, 2018), other parts of the neocortex , or PFC more specifically (Bhattacherjee et al, 2019), but we solely focused on using Layer 5 pyramidal neuron subtypes and their projection mapping as a case study to interrogate task encoding properties with a cell-type framework. Using PAG-projecting neurons as an example of molecular homogeneity due to our observation of its invariant clustering across multiple resolutions and methods (Figures 1E, S1B), we found that even a homogeneous transcriptomic class encodes diverse information.…”
Section: Discussionmentioning
confidence: 99%
“…The PFC data set (Bhattacherjee et al 2019) consists of cells from the prefrontal cortex of an adult mouse, and was generated using 10x Genomics Chromium v2 chemistry. Since only limited dynamics is expected in this data set, it is used here as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Different neuronal subtypes in mPFC play various roles in encoding and regulating behaviors 24 . To examine what are the specific types of neurons that involve in impulsive behaviors, we performed double-immunofluorescent staining of CaMKIIα and c-Fos (Fig.…”
Section: Postnatal Sevoflurane Exposure Showed Adhd-like Impulsive Bementioning
confidence: 99%